Method for preparing size-controllable high-crystallinity flaky silver powder

The method addresses the challenge of achieving high crystallinity and uniform size in flaky silver powder by using PVP K30, PVA, and ascorbic acid, resulting in high-dispersibility and low-temperature sinterable flaky silver powder for conductive applications.

CN119237726AActive Publication Date: 2025-01-03ZHU HAI JING RUI DIAN ZI CAI LIAO KE JI YOU XIAN GONG SI

Patent Information

Application Number
CN202411324407.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Existing methods for preparing flaky silver powder struggle to achieve high crystallinity and uniform particle size distribution, leading to agglomeration and poor dispersibility, which affects the performance of conductive silver paste in electronic components.

Method used

A method involving the use of polyvinyl pyrrolidone (PVP K30) as a dispersant, trisodium citrate for reduction, polyvinyl alcohol (PVA) as a capping agent, and ascorbic acid for controlled growth, combined with mechanical dispersion to produce flaky silver powder with a controllable single crystal structure.

Benefits of technology

The method results in high-crystallinity, size-controllable flaky silver powder with excellent dispersibility and printability, enabling low-temperature sintering and low resistance conductive films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237726A_ABST
    Figure CN119237726A_ABST
Patent Text Reader

Abstract

A method for preparing flaky silver powder with the controllable single-crystal structure size comprises the steps that firstly, a silver nitrate aqueous solution is prepared, then a dispersing agent polyvinylpyrrolidone aqueous solution is added and stirred to be uniform, and then a trisodium citrate aqueous solution is added for reacting to prepare nano-silver seed crystals; finally, adding a polyvinyl alcohol aqueous solution serving as an end-capping reagent into the solution, and coating PVA on the crystal face of the nano-silver seed crystal {100} through a grinding dispersion machine to form a nano-silver seed crystal mixed solution containing silver nitrate, polyvinylpyrrolidone and coated PVA; preparing a nitric acid aqueous solution and an ascorbic acid aqueous solution, mixing and adding the nitric acid aqueous solution and the ascorbic acid aqueous solution into a reaction kettle, adding the mixed solution containing silver nitrate, polyvinylpyrrolidone and the PVA-coated nano-silver seed crystal under a stirring condition, and mixing to generate a reduction reaction; the PH value is adjusted through nitric acid to control the reduction reaction speed, the growth direction of nano-silver seed crystals is controlled through PVA, the particle size growth size is controlled through polyvinylpyrrolidone, and finally the flaky silver powder with the controllable single-crystal structure size is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials science, and in particular to high-crystallinity flaky silver powder and a method for manufacturing the same, in particular to a method for preparing size-controllable high-crystallinity flaky silver powder. Background Art

[0002] High-crystallinity flaky silver powder has a relatively large specific surface area, stable chemical properties, and surface or line contact between particles, so it has good conductivity. It can replace spherical ultrafine silver powder to prepare silver paste for solar cells, medium and low temperature conductive paste, conductive adhesive, anti-static products, etc. It is an important functional material for electronic components. Affected by the rapid development of industries such as power semiconductors, electric vehicles, rail transportation, energy storage and ultra-high voltage transmission, the demand for electronic-grade flaky silver powder continues to rise.

[0003] At present, electronic devices are constantly developing towards miniaturization, and mainstream manufacturers require the use of ultra-fine, uniform chemical composition, high purity, high crystallinity (single crystal structure), and good dispersibility of flaky silver powder. In order to meet the future technical trend of miniaturization and high capacity of electronic components. It is urgent to study and prepare flaky silver powder with uniform particle size distribution, high tap density, high crystallinity, strong antioxidant ability and excellent dispersibility. These key indicators directly affect the performance of conductive silver paste.

[0004] The synthesis methods of single crystal flaky silver powder include: photoinduced conversion method, thermal conversion method, template method and chemical reduction method. Among them: photoinduced conversion method, thermal conversion method and template method are relatively complicated to operate, and the preparation and post-processing of templates are also relatively difficult, and the yield is also low; while the chemical reduction method has a higher yield and lower cost, and is a synthetic method that has attracted much attention.

[0005] In the prior art, Chinese patent CN102133645B discloses "an environmentally friendly method for preparing micron-sized triangular silver flakes", which involves dripping silver nitrate oxidation solution into glucose reduction solution, and then keeping the temperature at 75-95°C for 48-72h to obtain micron-sized triangular silver flakes. This method has a high reaction temperature and a long reaction time, and the prepared flaky silver powder is severely agglomerated. It cannot adapt to current applications.

[0006] Chinese patent CN102974837A discloses a "method for preparing flaky nano silver powder". The method preferably uses a temperature of 40-80°C to react a silver salt aqueous solution containing a surfactant with a ferrous solution to obtain irregularly shaped silver flakes. The flaky silver powder prepared by this method has a complicated reaction process, a long reaction time, and a low crystallinity of the product. It cannot be well applied to the current product development needs. Summary of the invention

[0007] In view of the above-mentioned technical problems in the prior art, the present invention provides a method for preparing flaky silver powder with a single crystal structure and controllable size. The method for preparing flaky silver powder with a single crystal structure and controllable size is to solve the technical problem in the prior art that it is difficult to achieve both high dispersibility and high crystallinity of flaky silver powder.

[0008] The present invention provides a method for preparing flaky silver powder with controllable single crystal structure size, comprising the following steps:

[0009] 1) A step of preparing nano silver seed crystals: first preparing a silver nitrate aqueous solution, wherein the mass concentration of the silver nitrate aqueous solution is 50.0-150.0 g / L, then adding a dispersant, wherein the dispersant is a polyvinyl pyrrolidone (PVP K30) aqueous solution, stirring evenly, wherein the mass concentration of the polyvinyl pyrrolidone aqueous solution is 50.0-150.0 g / L; the amount of the dispersant polyvinyl pyrrolidone is 2.0%-60.0% of the mass of the silver nitrate; after heating to 40-80° C., injecting a reducing agent, wherein the reducing agent is a trisodium citrate aqueous solution, wherein the mass concentration of the trisodium citrate aqueous solution is 1.0-10.0 g / L, and the amount of the trisodium citrate is 0.1%-1.0% of the mass of the silver nitrate; reacting to generate a nano silver seed crystal aqueous solution;

[0010] 2) a step of coating the nano-silver seed with an end-capping agent: adding an aqueous solution of polyvinyl alcohol (PVA) with a mass concentration of 0.5-10 g / L to the aqueous solution of the nano-silver seed obtained in step 1), using the aqueous solution of polyvinyl alcohol as an end-capping agent, wherein the amount of the polyvinyl alcohol is 0.1%-10.0% of the mass of the silver nitrate in step 1); coating the polyvinyl alcohol on the {100} crystal surface of the nano-silver seed with the grinding and dispersing machine to obtain an aqueous solution of the nano-silver seed containing coated PVA;

[0011] 3) A step of growing a nano silver seed crystal: adding a nitric acid aqueous solution with a mass concentration of 20.0-500.0 g / L and an ascorbic acid aqueous solution with a mass concentration of 10-350 g / L into a stainless steel reactor, wherein the amount of the nitric acid is 0.5%-15% of the mass of the silver nitrate in step 1), and the amount of the ascorbic acid is

[0012] 1) 50%-100% of the mass of silver nitrate in the reaction mixture; heating to 20-60° C., injecting the aqueous solution of nano-silver seed crystals containing PVA coated obtained in step 2) into the above-mentioned stainless steel reaction kettle under stirring conditions, mixing and reacting, and preparing flaky silver powder with controllable single crystal structure size.

[0013] Furthermore, in step 1), the injection rate of the reducing agent trisodium citrate aqueous solution is 0.1-10.0 liters / minute.

[0014] Furthermore, in step 3), the injection rate of the aqueous solution containing the PVA-coated nanosilver seed crystals is 1.0-100.0 liters / minute.

[0015] Furthermore, in step 2), the grinding and dispersing machine is a combination of a colloid mill and a disperser. The high tangential speed generated by the high-speed rotation of the rotor and the strong kinetic energy brought by the high-frequency mechanical effect cause the material to be subjected to strong mechanical and hydraulic shearing, centrifugal extrusion, liquid layer friction, impact tearing and turbulence in the narrow gap between the stator and the rotor, and the material is evenly and finely dispersed and emulsified.

[0016] The present invention first adds a PVP K30 aqueous solution to a silver nitrate solution to produce a colorless precursor solution. When a reducing agent trisodium citrate aqueous solution is added, a yellow transparent solution can be obtained, and the intensity of the yellow color will slowly increase over time. This is due to the silver nanoparticles crystallization formed by the reduction of silver ions after the addition of trisodium citrate. When the reaction temperature increases from 40 degrees to 80 degrees, it is observed that the color changes rapidly with the increase in temperature until it becomes dark yellow. It can be seen that Ag + The reduction rate of ions is closely related to temperature. Although the reduction can be carried out at room temperature, the reduction rate will be higher when the temperature rises. The dispersion effect and surface steric effect of PVPK30 in water can effectively inhibit the growth of silver nuclei. From the electron microscope imaging, it can be seen that the maximum diameter of silver nanoparticles is between 10-20 nanometers. In this way, a stable nanosilver seed aqueous solution can be obtained.

[0017] Secondly, polyvinyl alcohol (PVA) aqueous solution is added to the above-mentioned nano silver seed crystal aqueous solution as a capping agent, and PVA is coated on the {100} crystal face of the nano silver seed crystal by a grinding and dispersing machine. This is because the surface energy of different crystal faces of the nano crystals will be different. Through the strong interaction between the PVA capping agent and the crystal Ag crystal face, the PVA capping agent is more likely to be coated on the {100} crystal face of the silver nanoparticles, causing the silver seed crystals to tend to guide the growth of the {111} crystal face to form a pentagonal crystal structure. PVA as a surfactant not only caps the {100} crystal face, but also excessive provision of PVA will also cap the {111} crystal face. This situation will grow isotropically to form nanoparticles. Nano silver seed particles have a large specific surface area and a high specific surface energy, and are in a thermodynamically extremely unstable state. During the preparation and post-treatment process, particles are easily agglomerated and agglomerated to form secondary particles, which makes the particle size larger, and eventually loses the unique functions of the nano silver seed crystals when used. Therefore, the high shear force or impact force of the grinding and dispersing machine can make the nano silver seed particles evenly dispersed in the solution. At the same time, the special surface structure of the nano silver seed particles is easy to produce chemical adsorption under the action of shear force, forming organic compound branches or protective layers.

[0018] Finally, the above solution is injected into a mixture of ascorbic acid and nitric acid, stirred and mixed to cause a reduction reaction. The pH value is adjusted by nitric acid to control the reaction speed, the PVA end-capping agent controls the crystallization direction, and the polyvinyl pyrrolidone (PVP K30) dispersant controls the growth size of the silver seed crystals, and finally a high-crystallinity, size-controlled flaky silver powder is obtained. The silver flakes have a high specific surface area and excellent printability, and can be sintered at a relatively low temperature. Even if the firing temperature of the conductive silver paste is low, a conductive film with a low resistance value can be formed.

[0019] The invention adopts polyvinyl pyrrolidone (PVP K30) as a dispersant, uses trisodium citrate to reduce silver nitrate to prepare nano silver seeds, then uses PVA as a capping agent to control the growth direction of the silver seeds, finally reduces the silver nitrate with ascorbic acid, and controls the reaction speed by adjusting the pH value with nitric acid, and finally obtains size-controllable high-crystallinity flaky silver powder. After multiple experiments, a breakthrough has been made in the preparation of nano silver seeds and the verification of the growth process of flaky silver powder. The experimental foundation has been laid for the large-scale preparation of high-crystallinity flaky silver.

[0020] Compared with the prior art, the technical effect of the present invention is positive and obvious. Since the silver flakes according to the present invention can be fired at a relatively low temperature, the obtained flaky silver powder not only has high sintering activity, but also ensures the printing performance of the conductive silver paste prepared by the silver flakes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a process flow chart of a method for preparing flaky silver powder with controllable single crystal structure size.

[0022] Figure 2 It is a schematic diagram of the preparation, encapsulation and growth reaction of silver seed of the present invention.

[0023] Figure 3 This is a scanning electron microscope image of the silver powder prepared in Example 1.

[0024] Figure 4 This is a scanning electron microscope image of the silver powder prepared in Comparative Example 2.

[0025] Figure 5 This is a scanning electron microscope image of the silver powder prepared in Comparative Example 3.

[0026] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods. DETAILED DESCRIPTION

[0027] Example 1

[0028] like Figure 1 As shown, the present invention provides a method for preparing a single crystal structure with controllable size of flaky silver powder, comprising the following steps: (as Figure 1 (shown)

[0029] 1) Weigh 15 kg of silver nitrate and add it into a 200 L stainless steel reactor. Add 160 L of pure water and stir to prepare a silver nitrate aqueous solution (such as Figure 2 shown);

[0030] 2) Weigh 3 kg of PVP K30 dispersant and add 27 L of water to dissolve, then inject into the above silver nitrate aqueous solution, stir to dissolve, and heat to 65 ° C for preservation (such as Figure 2 shown);

[0031] 3) Weigh 35 grams of trisodium citrate and add 7.2L of water to stir and dissolve, then add it evenly to the silver nitrate solution in 2) at a flow rate of 0.28L / min. After adding the trisodium citrate aqueous solution, the reaction solution begins to turn into a yellow transparent solution (this is due to the silver nanoparticles crystallization formed by the reduction of silver ions after the addition of trisodium citrate). As time goes by, the intensity of the yellow color will slowly increase. After the injection of the trisodium citrate aqueous solution is completed, continue stirring for 20 minutes, and finally obtain nanosilver crystals with an average particle size of 10-30 nanometers (such as Figure 2 shown);

[0032] 4) Weigh 50g of PVA and add 10L of water to stir and dissolve, then add it to the aqueous solution containing nanosilver seeds described in 3) at a speed of 10L / min. After the injection of the PVA aqueous solution, turn on the grinding and dispersing machine (purchased from Shanghai Yiken Machinery Equipment Co., Ltd., model ER2000) and valve A, and the mixed liquid will enter the grinding and dispersing machine through the pipeline from the bottom of the 200L stainless steel reactor described in 1) above for grinding and dispersion, and circulate back to the 200L stainless steel reactor. After 30 minutes of cyclic reciprocating dispersion and grinding, PVA is finally coated on the {100} crystal surface of the nanosilver seeds to obtain an aqueous solution of nanosilver seeds coated with PVA; (such as Figure 2 (shown)

[0033] 5) Weigh 12 kg of ascorbic acid and add it into a 500 L stainless steel reactor, add 228 L of pure water and stir to prepare an ascorbic acid aqueous solution (such as Figure 2 shown);

[0034] 6) Weigh 25 L of nitric acid aqueous solution with a mass concentration of 20 g / L and add it to the ascorbic acid aqueous solution described in 5) above, and heat to 60° C. with stirring;

[0035] 7) Close valve A, open constant flow pump and valve B under stirring to inject the aqueous solution of nano silver seed crystals containing PVA coated in 4) into the 500L stainless steel reactor in 5) at a speed of 25 liters / minute. After the addition, the solution in the stainless steel reactor quickly changes color to light black, and then gradually changes to gray, which is due to the color of the flaky silver particles. After the injection is completed, stir and mix for 10 minutes to obtain a gray silver slurry suspension (such as Figure 2 shown);

[0036] 8) The reaction solution of step 7) is transferred to a centrifuge filter bag, the clear liquid is filtered out first, and the pure water spray device is turned on to wash the silver powder. After one hour, the conductivity of the filtered water is tested to be 20 μs / cm. At this time, the pure water spray washing is stopped, and the silver powder is dried by a high-speed rotating centrifuge to finally obtain flaky silver particles with a water content of less than 12% by mass;

[0037] 9) transferring the loose flaky silver powder coarse particles to a device with a drying device for drying at a temperature lower than 65° C. to obtain dry flaky silver powder after 8 hours;

[0038] The electron microscope image shows uniformly dispersed silver particles ( Figure 3 As shown). The flaky silver powder particles have a single crystal structure, and the crystal grains are pentagonal. The cumulative 50% particle size (D50) in the volume-based particle size distribution obtained by the silver powder particle size distribution measuring device by wet method is 1.75um. When it is used as a material for conductive silver paste, even if the firing temperature of the conductive silver paste is low, a conductive film with a low resistance value can be formed.

[0039] Take 250 grams of the above silver powder, 3.8 grams of ethyl cellulose and 46.2 grams of butyl carbitol, and carry out a mixed degassing operation for 60 seconds through a planetary centrifugal stirring / degassing device (AR250 produced by Thinky). The obtained mixture is kneaded by a three-roll grinder with a roller gap of 90um-60um-20um to obtain a conductive paste. The conductive paste is screen-printed on an alumina substrate into a rectangular film with a size of 8mm x 10mm, and then dried at 200°C for 20 minutes in a hot air circulation drying oven. Finally, a high-temperature box furnace is used to heat the substrate at 400°C for 15 minutes to prepare a conductive film.

[0040] The specific resistance value of the silver conductive film was calculated to be 2.8 μΩ·cm based on the surface resistance measured by a surface resistance measuring device and the film thickness measured by a film thickness measuring instrument.

[0041] Comparative Example 2

[0042] like Figure 1 As shown, the present invention provides a method for preparing flaky silver powder with controllable single crystal structure size, the steps are the same as those in Example 1, only the grinding and dispersing machine is not used to disperse the nano silver seeds to encapsulate the PVA.

[0043] The obtained silver powder electron microscopy image ( Figure 4 As shown in the figure, the silver powder particles are composed of a mixture of many quasi-spherical silver powders and flaky silver powders. This indicates that PVA as an end-capping agent does not effectively wrap the {100} crystal plane of the nano-silver seed, causing the growth rate of the silver seed along each crystal plane to be basically the same, resulting in the nano-silver particles tending to grow in a spherical shape, forming granular silver powder.

[0044] Comparative Example 3:

[0045] like Figure 1 As shown, the present invention provides a method for preparing flaky silver powder with controllable single crystal structure size, the steps are the same as those in Example 1, only the PVA end-capping agent is not added.

[0046] The obtained silver powder electron microscopy image ( Figure 5 As shown in FIG. 1 ). The silver powder particles are quasi-spherical silver powder. The absence of PVA end-capping agent on the surface to wrap the {100} crystal plane of the nano-silver seed will cause the growth rate of the silver seed along each crystal plane to be basically the same, resulting in the nano-silver particles tending to grow in a spherical shape, forming granular silver powder.

[0047] Therefore, the present invention proposes a method for preparing a flaky silver powder with a controllable single crystal structure size. The flaky silver powder prepared by the method can form a single crystal structure, has high dispersibility and is easy to control the size of the silver flakes. The production method is simple and fast, and the prepared flaky silver powder has a huge market demand.

Claims

1. A method for preparing flaky silver powder with controllable single crystal structure size, characterized in that: The steps include: 1) A step of preparing nano silver seed crystals: first preparing a silver nitrate aqueous solution, wherein the mass concentration of the silver nitrate aqueous solution is 50.0-150.0 g / L, then adding a dispersant, wherein the dispersant is a polyvinyl pyrrolidone aqueous solution, stirring evenly, wherein the mass concentration of the polyvinyl pyrrolidone aqueous solution is 50.0-150.0 g / L; the amount of the polyvinyl pyrrolidone is 2.0%-60.0% of the mass of the silver nitrate; heating to 40-80° C., then injecting a reducing agent, wherein the reducing agent is a trisodium citrate aqueous solution, wherein the mass concentration of the trisodium citrate aqueous solution is 1.0-10.0 g / L, and the amount of the trisodium citrate is 0.1%-1.0% of the mass of the silver nitrate; reacting to generate a nano silver seed crystal aqueous solution; 2) a step of coating the nano-silver seed with an end-capping agent: adding a polyvinyl alcohol aqueous solution with a mass concentration of 0.5-10 g / L to the nano-silver seed aqueous solution obtained in step 1), using the polyvinyl alcohol aqueous solution as an end-capping agent, and the amount of polyvinyl alcohol used is 0.1%-10.0% of the mass of the silver nitrate in step 1); coating the polyvinyl alcohol on the {100} crystal surface of the nano-silver seed with a grinding and dispersing machine to obtain a nano-silver seed aqueous solution containing coated PVA; 3) a step of growing a nano silver seed crystal: adding a nitric acid aqueous solution with a mass concentration of 20.0-500.0 g / L and an ascorbic acid aqueous solution with a mass concentration of 10-350 g / L into a stainless steel reactor, wherein the amount of the nitric acid is 0.5%-15% of the mass of the silver nitrate in step 1), and the amount of the ascorbic acid is 50%-100% of the mass of the silver nitrate in step 1); heating to 20-60° C., injecting the nano silver seed crystal aqueous solution containing coated PVA obtained in step 2) into the above stainless steel reactor under stirring, mixing and reacting, and preparing a single crystal structure with controllable size flaky silver powder.

2. The method for preparing flaky silver powder with controllable single crystal structure size according to claim 1, characterized in that: In step 1), the injection rate of the reducing agent trisodium citrate aqueous solution is 0.1-10.0 liters / minute.

3. The method for preparing flaky silver powder with controllable single crystal structure size according to claim 1, characterized in that: In step 3), the injection rate of the aqueous solution containing the PVA-coated nano-silver seed crystals is 1.0-100.0 liters / minute.

Citation Information

Patent Citations

  • Preparation method of flakelike nano silver powder

    CN107377989A

  • Preparation method of round-cake-shaped sheet type superfine silver powder

    CN110238385A

  • Thin single-crystal lamellar silver powder synthesized by chemical method and preparation method thereof

    CN110899722A

  • Method for regulating and controlling crystallite size of silver powder

    CN117086323A

  • Preparation method of superfine silver powder for low-temperature silver paste

    CN117300138A

Cited By

  • Flaky silver powder with low apparent density as well as preparation method and application of flaky silver powder

    CN119819916A

  • Micro-nano silver powder with controllable particle size and preparation method thereof

    CN120190346A

  • Micro-nano silver powder with controllable particle size and preparation method thereof

    CN120190346B

  • Preparation method of silver powder for efficient photovoltaic electrode

    CN121244931A